2020
DOI: 10.3892/mco.2020.2036
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for upstaging of ductal carcinoma in situ (DCIS) to invasive carcinoma in non‑mass‑type DCIS

Abstract: Preoperatively diagnosed ductal carcinoma in situ (DCIS) is sometimes upstaged to invasive cancer by postoperative pathological examination. Various preoperative factors associated with upstaging to invasive cancer have been reported; however, this subject remains to be clarified. DCIS takes various forms on imaging, but many cases show non-mass-type lesions. In non-mass-type DCIS, recognizing the presence of invasion is difficult. To investigate predictors associated with upstaging to invasive cancer more pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…[ 41 ] and Oda et al . [ 42 ] Necrosis 10% (n = 12) and microcalcification 3.33% (n = 4) were incidental findings in our study. None of these cases had a prior history of trauma, radiotherapy, and reduction mammoplasty or breast infection.…”
Section: Discussionsupporting
confidence: 47%
“…[ 41 ] and Oda et al . [ 42 ] Necrosis 10% (n = 12) and microcalcification 3.33% (n = 4) were incidental findings in our study. None of these cases had a prior history of trauma, radiotherapy, and reduction mammoplasty or breast infection.…”
Section: Discussionsupporting
confidence: 47%
“…When present on biopsy, comedonecrosis is also found to predict upstaging to invasive carcinoma. 6 In most (but not all) clinical studies, DCIS with low-or intermediate-nuclear grade was considered high-grade/high-risk if comedonecrosis was present. 18,23,24 However, there is significant variability in the diagnostic threshold for comedonecrosis regarding the extent of the duct diameter involved by necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This conservative approach has been supported by the results of a previous meta‐analysis, which concluded that even with biopsy alone, the mortality rate of patients with DCIS remained at only 17.8% within at least a 15‐year follow‐up, with a steep increase to 55.2% for those with invasive local recurrence 5 . Thus, a correct risk stratification of these precursor lesions is fundamental when planning treatment strategies, and possible predictors for upstaging ductal DCIS to invasive carcinoma have been identified, such as palpability, tumour size, radiological features, biopsy methods, and histological grading 6–9 . Nevertheless, this process is limited by the significant interobserver variability in the grading of DCIS by human pathologists, as demonstrated in previous studies 10,11 …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Oda et al reported a 27% upgrade (DCIS to IDC) for non-mass, with a higher likelihood when palpable, although imaging lexicons, including clustered rings, did not show a consistent trend [ 23 ]. Further study is necessary to determine whether the imaging lexicons suggest invasion.…”
Section: Introductionmentioning
confidence: 99%